Phosphoproteomic Profiling of Selenate-Treated Alzheimer's Disease Model Cells - Chen, Ping (PLoS One, 2014)
The reversible phosphorylation of proteins regulates most biological processes, while abnormal phosphorylation is a cause or consequence of many diseases including Alzheimer's disease (AD). One of the hallmarks of AD is the formation of neurofibrillary tangles (NFTs), which is composed of hyperphosphorylated tau proteins. Sodium selenate has been recently found to reduce tau hyperphosphorylation and NFTs formation, and to improve spatial learning and motor performance in AD mice. In the current study, the phosphoproteomics of N2aSW cells treated with selenate were investigated. To avoid missing low-abundance phosphoproteins, both the total proteins of cells and the phosphor-enriched proteins were extracted and subjected to the two-dimensional gel electrophoresis with Pro-Q diamond staining and then LC-MS/MS analysis. A total of 65 proteins were altered in phosphorylation level, of which 39 were up-regulated and 26 were down-regulated. All identified phosphoproteins were bioinformatically annotated according to their physiochemical features, subcellular location, and biological function. Most of these significantly changed phosphoproteins are involved in crucial neural processes such as protesome activity, oxidative stress, cysteine and methionine metabolism, and energy metabolism. Furthermore, decreases were found in homocysteine, phosphor-tau and amyloid β upon selenate treatment. Our results suggest that selenate may intervene in the pathological process of AD by altering the phosphorylation of some key proteins involved in oxidative stress, energy metabolism and protein degradation, thus play important roles in maintaining redox homeostasis, generating ATP, and clearing misfolded proteins and aggregates. The present paper provides some new clues to the mechanism of selenate in AD prevention.